Gender differential in social and economic predictors of incident major depressive disorder in the Ibadan Study of Ageing - Ojagbemi, Akin (Soc Psychiatry Psychiatr Epidemiol, 2018)
PURPOSE: Working on the hypothesis that the social and economic factors associated with onset of late-life depression operate differently for men and women, we investigated the impact of current social relationships and lifetime occupational attainment on incident major depressive disorder (MDD) assessed in three follow-up waves over a period of 5 years. METHODS: Participants were part of a household multistage probability sample of 2149 Nigerians who were aged 65 years and above. The presence of current and lifetime MDD was assessed using the World Health Organization (WHO) Composite International Diagnostic Interview. Participants’ highest occupational attainment was categorised based on the International Standard Classification of Occupations, while socio-economic positions were estimated using asset-based measures relevant to low-income settings. Current social contacts and participation were assessed using items from the WHO Disability Assessment Schedule. RESULTS: We found an incidence rate of 120.9 per 1000 persons years (95% CI = 110.4–132.5) among 1394 persons who were free of lifetime MDD and dementia at baseline. Incidence rates were 94.7 (95% CI = 82.5–108.7) and 153.8 (136.3–173.6) per 1000 person years, in men and women respectively. In analyses comparing gender and adjusting for the effect of age, we found that while a lifetime of unskilled occupation (trade: HR = 1.4, 95% CI = 1.0–2.0, and elementary occupations: HR = 1.5, 95% CI = 1.1–2.1) was significantly associated with incident MDD in men (but not in women), living in a rural location (HR = 1.3, 95% CI = 1.0–1.7) and having no regular contact with family (HR = 2.2, 95% CI = 1.0–4.7) at baseline significantly predicted subsequent onset of MDD in women. CONCLUSION: There was a gender differential in the association of social and economic factors with incident MDD in this sample. These findings have implications for the design of early prevention strategies for late-life depression in sub-Saharan Africa. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00127-018-1500-7) contains supplementary material, which is available to authorized users.